2021
DOI: 10.2355/isijinternational.isijint-2020-744
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaF<sub>2</sub> on Viscosity and Refining Ability of Highly Basic Slags for Duplex Stainless Steel

Abstract: To optimize CaF 2 content in highly basic CaO-18%Al 2 O 3-SiO 2-10%MgO-CaF 2 (%CaO/%SiO 2 = 6, denoted as C/S = 6) refining slags used for the production of Al-killed duplex stainless steel with high cleanliness demand, the effect of CaF 2 content on the viscosity and refining ability of the slags were studied and compared with typical CaF 2-free highly basic CaO-30%Al 2 O 3-SiO 2-10%MgO (C/S = 6) slag. The effect of CaF 2 addition in decreasing slag viscosity becomes less obvious with increasing temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
(98 reference statements)
2
4
0
Order By: Relevance
“…Therefore, the inclusions remained in a semiliquid state. As observed in previous studies, [ 43 ] semiliquid inclusions can also take on a spherical shape (Figure 3b).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the inclusions remained in a semiliquid state. As observed in previous studies, [ 43 ] semiliquid inclusions can also take on a spherical shape (Figure 3b).…”
Section: Resultssupporting
confidence: 86%
“…Therefore, the inclusions remained in a semiliquid state. As observed in previous studies, [43] semiliquid inclusions can also take on a spherical shape (Figure 3b). Figure 11 presents the elemental mapping of rare-earth inclusions in the samples taken at 3 and 10 min after Ce addition.…”
Section: The Chemical Compositions Of the Nonmetallic Inclusionssupporting
confidence: 86%
“…Figure 2(a) describes the viscosity variations of SA1-SA5 slags (containing different Al 2 O 3 contents) within the temperature range of 1 753-1 873 K. The viscosities measured by Zheng et al 11) for 55%CaO-9%SiO 2 -18%Al 2 O 3 -10%MgO-8%CaF 2 slag, which has a similar composition to SA3 were also shown in Fig. 2(a).…”
Section: Effect Of Al 2 O 3 Content On Slag Viscositymentioning
confidence: 68%
“…Extensive studies have revealed that both Al 2 O 3 and CaF 2 significantly affect slag viscosity. [11][12][13] However, excessive CaF 2 addition will accelerate the corrosion of refractories and induce serious environmental pollution. 13,14) By comparison, appropriate Al 2 O 3 addition can not only enhance the refining effect but also be friendly to the environment.…”
Section: Effect Of Al 2 O 3 On Viscosity and Refining Ability Of High...mentioning
confidence: 99%
“…Bearing steel [88] 50.4 4.3 40.3 5 -Alloy structural steel [89] 47.5 12.5 12. Reproduced with permission.…”
Section: Al 2 Omentioning
confidence: 99%